Defining personnel marketing strategies - Olena Gladka; Viktoriya Fedorova (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The purpose of the study is to develop methodological basis as to the justification and selection of personnel marketing strategy based on logical analysis and systematic approach. The strategy is suggested to be developed taking into consideration external personnel marketing strategy and internal one. The former is based on the capacity of an employer to meet expectations of potential personnel and is aimed at forming enterprise's external attractiveness as an employer. The latter is based on the capacity of an employer to satisfy expectations of existing personnel and is aimed at forming enterprise's internal attractiveness as an employer. The choice of strategy is based on the Matrix determining the generalized level of enterprise's attractiveness as an employer. This Matrix allows identifying nine types of personnel marketing strategies. The content of each type of personnel marketing strategy was substantiated. The main actions contributing to the improvement of level of enterprise's attractiveness as an employer internally and externally were developed based on the 7Ps personnel marketing mix. Results of this study have theoretical and practical significance. They can be used as basis for further studies, while developed recommendations can be used by a management team for implementation within an enterprise that seeks to develop its employer attractiveness.
Keywords: L21; M1; M31; Z22; 650; personnel marketing strategy; personnel marketing; employer's attractiveness; personnel marketing strategy matrix; 7Ps personnel marketing mix